The relationship between human – computer interaction with educational psychology in Medan: Hubungan interaksi manusia dan komputer dengan psikologi pendidikan di Kota Medan - Fikri Irfan Sahputra; Filia Dina Anggaraeni (Talenta Publisher, 2022)
This study examines the relationship between human and computer interactions in educational psychology. This study used simple random sampling. participants in this study collected 100 participants who used the mind map learning method in the Educational Psychology course in Medan. Analysis of the data in this study using Spearman correlation produces a significance value of 0.695 with an r-value of 0.040. The results of this study indicate insignificant relationship between human and computer interaction and educational psychology which is used through the use of applications for complex learning materials for educational psychology courses.